2013
DOI: 10.4028/www.scientific.net/amm.393.931
|View full text |Cite
|
Sign up to set email alerts
|

Application of Response Surface Methodology to Predict Oil-Film Friction in Journal Bearing

Abstract: Oil-film friction response is one of the key parameters that describe the operating conditions in hydrodynamic lubrication regimes. In the present paper, response surface methodology (RSM) with Box-Behnken experiment Design technique (BBD) has been utilized to predict and evaluate the effects of the three-level-three-independent variables on the oil-film friction. The design independent variables including rotational speed, load and oil-feed pressure were used to develop an empirical model for the oil-film fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…RSM is one of the most widely used technique for optimization in design of experiment (DOE) concept. The basis for DOE is to allow analysis of the interactions between input variables and related output variables for identification of the optimal response within the experimental region (Ahmed et al, 2013;Wu et al, 2012;Qiu et al, 2013).…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…RSM is one of the most widely used technique for optimization in design of experiment (DOE) concept. The basis for DOE is to allow analysis of the interactions between input variables and related output variables for identification of the optimal response within the experimental region (Ahmed et al, 2013;Wu et al, 2012;Qiu et al, 2013).…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…Beberapa penelitian yang pernah dilakukan salah satunya yaitu analisis kondisi optimum pencahayaan, kebisingan dan temperatur dengan metode response surface [3]. Penelitian yang dilakukan oleh [4] pada respon oil-film friction menggunakan metode response surface memberikan hasil yang baik dan dapat memprediksikan dengan tepat. Penelitian yang dilakukan oleh [5] menerapkan metode response surface untuk optimalisasi laba penjualan tanaman kangkung darat.…”
Section: Pendahuluanunclassified
“…Pandian et al [11] studied a twin cylinder compression engine to analyse the effect of injection system parameters on power output and emission characteristics while running in pongamia biodiesel-diesel blend considering RSM. Ahemad et al [12] utilized the RSM to study oil film friction of a fluid film bearing and compared the predicted and observed parameters with good agreement. Lee et al [13] further considered the response surface methodology for a HSDI diesel engine using common rail injection system.…”
Section: Introductionmentioning
confidence: 99%